Adaptive skills and mental health in children and adolescents with neuromuscular diseases. (January 2021) - Gosar, David; Košmrlj, Lejla; Musek, Petra Lešnik; Meško, Tamara; Stropnik, Staša; Krkoč, Vesna; Golli, Tanja; Butenko, Tita; Loboda, Tanja; Osredkar, Damjan
Abstract: Background: Adaptive skills represent the ways that children and adolescents meet their basic needs for self-care, decision making, communication, and learning in their daily life. Having a neuromuscular disease (NMD) not only presents mental health issues, but also impacts these skills. Aims: Our study aimed to compare the adaptive skills and mental health of paediatric patients with the most common NMDs with their healthy peers and assess how NMDs shape the way patients form relationships with others, engage in leisure activities and take care of their daily living needs. Methods: We used the Adaptive Behaviour Assessment System (ABAS-3) and Achenbach Child Behaviour Checklist (CBCL) to compare the adaptive skills and mental health symptoms of 50 NMD patients to a demographically-matched control group of 298 peers. We examined specific outcomes of having myotonic dystrophy (DM), Duchenne muscular dystrophy (DMD), Becker muscular dystrophy (BMD), spinal muscular atrophy (SMA) or a mixed group of other NMDs. Results: All NMD patients displayed poor practical adaptive skills. When the disease was more likely to involve the central nervous system (DM, DMD) they also showed additional deficits in their conceptual and social skills. Contrary to previous research no increased rate of psychopathological symptoms was found in NMD patients, with the exception of difficulties in the social domain among patients with DM. Conclusions: Although most children with NMDs displayed more limited practical skills, the specific profile of adaptive skills for each patient group needs to be taken into consideration when planning school support and other psychosocial interventions. Highlights: Limited adaptive skills are common in pediatric patients with the most prevalent neuromuscular diseases (NMDs). NMDs that impact the central nervous system (DM1, DMD) are associated with deficits in conceptual and social skills. Psychosocial functioning is more adversely affected in NMDs with co-morbid intellectual disability (DM1, DMD > SMA).